Housing Affordability In Nigeria: A Comparative Analysis Of Beneficiaries And Non-Beneficiaries Of Organized Private Sector Housing - Adegoke, Samson Akinbamide Omobayo (Advances in Social Sciences Research Journal, 2021)
Housing delivery in Nigeria has been dominated by the On-Site-Builders, each building incrementally as private individual for his household. The need to take advantage of economy of scale in housing delivery to enhance affordability led to the emergence of Organized Private Sector Housing Delivery in Nigeria. Despite this initiative, the majority of the people are not accessing housing from the Organized Private Sector Housing Developers, still employing their incremental housing approach. This study is therefore a comparative analysis of housing affordability of beneficiaries and non-beneficiaries of Organized Private Sector Housing Delivery in Nigeria. A cross-sectional survey design was adopted. The respondents, beneficiaries and non-beneficiaries, were selected by systematic random sampling technique. Ten percent of beneficiaries’ household heads were selected from the occupied houses (19500) in the estates. The respondents among the non-beneficiaries were selected among the occupied housing units within 1km radius of the houses around each of the sampled estates until equal numbers of respondents from beneficiaries was selected, where possible. Thus, there were 1,950 and 1,332 number of respondents among beneficiaries and no-beneficiaries respectively. The structured questionnaire administered on the heads of households’ elicited information on demographic characteristics (age, sex, household size, etc) and housing affordability variables such as (household income, housing expenditure, access to mortgage, other non-housing expenditure, etc). The questionnaire administered on Organized Private Sector Housing Developers (OPSHDs) seeks information on types of houses produced, selling prices, sales terms, among others. We rely on affordability rating scale of: normal ≤30%; tolerable 30.1-50% and stressed ≥50% to measure and compare housing affordability of beneficiaries and non-beneficiaries. They study revealed that while about 42% of beneficiaries fall within normal housing affordability, about 76% of non-beneficiaries are in that category. About 37% of beneficiaries are in tolerable housing affordability category while only about 16% of non-beneficiaries are there. Those under varying degrees of housing affordability stress are about 21% and 8% among beneficiaries and non-beneficiaries respectively. The major policy implication of the findings is that direct support to non-beneficiaries – the On-Site-Builders by government, through serviced plots and mortgage facility may be a more veritable approach for resolving the current housing crisis in the country.